A review on bioconversion processes for hydrogen production from agro-industrial residues. (30th October 2022) - Saravanan, A.; Kumar, P. Senthil; Mat Aron, Nurul Syahirah; Jeevanantham, S.; Karishma, S.; Yaashikaa, P.R.; Chew, Kit Wayne; Show, Pau Loke
Abstract: Hydrogen is a renewable gas, efficient to produce energy that makes it a suitable alternative and effective solution for a carbon-free environment. Unlike other fossil fuels, combustion of hydrogen does not produce toxic compounds, such as greenhouse gases, carbon monoxide, hydrocarbons, etc., resulting in less environmental pollution. Agro-industrial residues contain several lignocelluloses that favor the growth of microorganisms to produce valuable products such as hydrogen. Of the diverse techniques in hydrogen production, bioconversion proves to be an efficient method in permuting agro-industrial residues into hydrogen. This review provides detailed information on the bioconversion processes and factors involved in hydrogen production from agro-industrial residues including different fermentation processes such as dark fermentation and photo-fermentation, and fuel cell systems such as microbial electrolysis cell and microbial fuel cell. Different pretreatment techniques to enhance the availability of lignocellulose for hydrogen production have been elaborated in this review. Various factors including pH, temperature and nutrient composition of feed, affecting the production efficiency and purity of the products during fermentation have been discussed. Graphical abstract: Image 1 Highlights: Agro-industrial residues are suitable feedstock for hydrogen production. Difficulties and future perspectives of biohydrogen conversion are discussed. Coupling of dark fermentation with MEC increases net energy gain. Integration of MEC and MFC shows potential over conventional techniques.